Foreign language vocabulary teaching in the presentation of foreign methodologies: diachronic and synchronic interpretation - O. G. Shcheglova; N. L. Moskovskaya (Вестник Северо-Кавказского федерального университета, 2024)
Introduction The article analyzes the views of foreign researchers on the problem of teaching lexis, and also identifies the tasks of learning words, analyses interpretations of the concept “vocabulary”, considers the relationship between vocabulary and grammar. Particular attention is drawn to the discrepancy between the views of national and foreign researchers on the issue under discussion, which is due to the difference in the contexts of teaching languages, namely – the lack of the language environment and the formalized nature of learning. Meanwhile, the experience of foreign theorists and language teaching practitioners is of great interest and deserves close attention.Goal. The goal of the article is to identify problems and prospects for the study of words.Materials and methods. The study is based on the analysis of the views of foreign researchers on the problem of teaching the lexis.Results and discussion. During the research work, a number of important points of the communicative approach were discovered as a whole and the special significance of vocabulary in the formation of communicative competence as the ability to communicate. The methodological consequences of the modern lexical approach were noted.Conclusion. Based on the results of the study it can be concluded that the biggest problem is the imbalance of language, pseudo-speech and speech types of exercises and communicative tasks with the obvious dominance of outdated activities that do not develop oral speech skills.